Diversidade beta e estrutura de interações em redes inseto-planta do cerrado - Martins, Lucas Pereira (2018)
Understanding how species interact with each other is essential to advance our knowledge on community ecology. However, there are still gaps regarding how interspecific interactions affect and are affected by the variation in the composition of species that constitute the ecological networks. In particular, studies of beta diversity are interesting to understand how sets of biotic filters may affect species’ geographic distribution and persistence on communities. Another interesting question is if variations in species composition may cause changes on how ecological networks are structured. In this dissertation, we propose to evaluate patterns of beta diversity and structure on insect-plant interaction networks. Specifically, in the first chapter we aimed to test if beta diversity is affected by the trophic level to which the assemblage belongs, and by the degree of specialization of species at higher trophic levels to their host species. For this, we used a tritrophic system comprising plants of the family Asteraceae, endophagous herbivores and parasitoids sampled in remnants of Brazilian Cerrado. Our main results show that total beta diversity of parasitoids (higher trophic level) was lower than those of the other trophic levels, while there was no difference between total beta diversity of plants and herbivores. Furthermore, the degree of specialization of the assemblages of herbivores and parasitoids was positively associated to the beta diversity of these groups. In the second chapter, we evaluated if species beta diversity among sites affects dissimilarity in network structure, and if this relationship changes across time. Overall, the relationship between spatial beta diversity and dissimilarity in plant-herbivore network structure was context-dependent, thus indicating that different ecological processes (i.e., niche-based and neutral) may drive the organization of antagonistic networks across time.